High molecular weight polylactic acids by polyesterification using diisopropylcarbodiimide (DIPC) and 4-(dimethylamino) pyridinium ptoluene sulfonate (DPTS) - Shyamroy, S.; Garnaik, Baijayantimala; Sivaram, S. (Polymer Bulletin, 2015)
High molecular weight poly(l-lactic acid) has been prepared from the corresponding functionally terminated oligomers employing a polyesterification method at room temperature using diisopropylcarbodiimide and 4-(dimethylamino) pyridinium-p-toluene sulfonate. Self-condensation of hydroxyl and carboxylic acid-terminated poly(l-lactic acid) oligomers (M (n) : similar to 1,000) resulted in polymers with high molecular weights (M (n) > 45,000) under mild conditions. End-group analysis by MALDI-TOF provided evidence for N-acylurea formation in the product under the reaction conditions employed.